Angangueo: descubrimiento y consolidación de un centro minero. 1792-1810 - Lemus García, Eduardo (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
This thesis focuses on studying mines of Angangueo, which was discovered at the end of the colonial order and therefore had a different development of other nearby centers the real, we start from the study of the eastern region of the State of Michoacan, the which allowed us to analyze the development of the region since its configuration as the hacienda Jesus Nazareno de Angangueo, the discovery of the silver veins in their places in 1792, to its configuration as a seat for mines deputation. Another issue that did not interest analysis was the interference of local authorities in the surrounding mining centers as Tlalpujahua, Zitacuaro and Ixtlahuaca in shaping the population and the creation of mining infrastructure, and the extent of the production of silver in this location.

Este trabajo de tesis se centra en estudiar el real de minas de Angangueo, el cual fue descubierto a fines del orden colonial y por lo tanto tuvo un desarrollo diferente de otros centros aledaños, partimos del estudio de la región Oriente del Estado de Michoacán, lo cual nos permitió analizar el desarrollo de la región desde su configuración como la hacienda Jesús Nazareno de Angangueo, el descubrimiento de las vetas argentíferas en sus parajes en 1792, hasta su configuración como asiento de minas y diputación minera. Otro tema que no interesó analizar fue la injerencia de autoridades locales de los centros mineros aledaños como Tlalpujahua, Zitácuaro e Ixtlahuaca en la conformación de la población y la creación de infraestructura minera, así como el alcancé de la producción de la plata en esta localidad.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2016-0835; Opción en historia regional continental; Angangueo; Minería; Diputación; Colonia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/290